Action Line: blessing or curse? - David A. Zarkin (Journal of Applied Communications, 1973)
Agricultural College editors should consider the proposition that they may have a role in "action line," "action post," and similar columns that seek to provide newspaper readers with solutions to the complexities of life in 20th Century America.